(untitled) (Plant Tissue Culture and Biotechnology, 2018)
An efficient indirect plant regeneration protocol was developed for Viola canescens, an important medicinal herb used in broad spectra of diseases in number of folk medicines since aeon. Excessive use of this plant without any rehabilitating measure has led to decline its natural population. Present investigation reports the use of zeatin to regenerate the plant from the callus on MS following its acclimatization on the soil condition. Calli of the plant responded positively to zeatin and maximum number of shoots 13.07 ± 2.01 were obtained when 9.12 μM concentration of zeatin was used. Regenerated shoots were subsequently rooted with IBA on MS and half strength MS and showed maximum number of roots 14.13 ± 1.64 after 60 days when medium was fortified with 4.92 μM IBA, followed by transferring them to soil condition, acclimatization of the plantlet was carried in growth chamber and then finally to the field for their survival where it showed 80% survival. Plant Tissue Cult. & Biotech. 28(2): 215-222, 2018 (December)